Using an effective surface charge to explain surface potentials of Langmuir monolayers from dialkyldimethylammonium halides with the Gouy-Chapman theory - Cavalli, A.; Dynarowicz-Latka, P.; Oliveira, O. N.; Feitosa, E. (Elsevier B.V., 2001)
The use of an effective surface charge density has allowed the Gouy-Chapman (CC) theory to explain surface potential isotherms of Langmuir monolayers of dioctadecyldimethylammonium bromide (DODAB). The effective surface charge density of DODAB monolayer increases with the electronegativity of the counterions in the subphase. The pressure-area isotherms indicate a very condensed monolayer for DODAB spread on an I--containing subphase, which exhibits the lowest surface charge density, whereas the monolayer on a F-containing subphase is extremely expanded owing to the high surface charge density or electrostatic repulsion between headgroups. (C) 2001 Published by Elsevier B.V. B.V.